Acute psychological stress does not influence joint position reproduction performance in the elbow joint. - Adam Koncz; Ferenc Köteles; Blanka Aranyossy; Áron Horváth (PLoS ONE)
Background Proprioceptive accuracy is an important aspect of motor functioning thus understanding how the stress response affects it can broaden our knowledge about the effects of stress on motor performance. There has been published only one quasi-experimental study on this topic to date, reporting a negative association between stress and proprioceptive accuracy. The aim of the present study was to explore whether the stress response influences proprioceptive accuracy in a randomized and controlled experimental setting. Method Participants (Mage =  20.4 yrs, SDage =  1.91 yrs) were randomly assigned to a stress (n =  29) and a control (n =  28) group. Psychological stress was induced via an online quiz involving time pressure and instant feedback on performance. Participants' perceived (state anxiety) and physiological (heart rate, heart rate variability, skin conductance level) stress response and proprioceptive accuracy (the active and passive version of the Joint Position Reproduction test for the elbow joint) were measured before and after the experimental manipulation. Results The quiz substantially increased only participants' perceived stress however, proprioceptive accuracy was not impacted by the experimental manipulation. Conclusion Perceived stress does not impact proprioceptive accuracy.